Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/00004728-200607000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Arteriosclerotic Changes in the Intracranial Carotid Artery Using the Calcium Score Obtained on Plain Cranial Computed Tomography Scan

Abstract: There were a positive correlation between calcium scores on CT and angiographic changes of arteriosclerosis in the siphon as well as bifurcation, indicating angiographic changes can be predicted using calcium scores. However, the degree of calcification in the siphon cannot be used to predict the possibility of a future cerebral stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 11 publications
3
46
0
Order By: Relevance
“…Because our results indicate that for symptomatic patients, there is no relation between the degree of stenosis and the severity of stenosis, this finding may support the idea of soft atherosclerotic plaques being more of a risk for stroke than hard calcified plaques, [13][14][15][16] which are associated with plaque stability, and supports the premise that (nonsubendothelial) plaque calcification is associated with plaque stability. This idea is supported by the fact that the occluded arteries had an average calcium volume score of only 0.04 mL.…”
Section: Discussionsupporting
confidence: 66%
“…Because our results indicate that for symptomatic patients, there is no relation between the degree of stenosis and the severity of stenosis, this finding may support the idea of soft atherosclerotic plaques being more of a risk for stroke than hard calcified plaques, [13][14][15][16] which are associated with plaque stability, and supports the premise that (nonsubendothelial) plaque calcification is associated with plaque stability. This idea is supported by the fact that the occluded arteries had an average calcium volume score of only 0.04 mL.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, in 2 cross-sectional studies, 8,9 they found that intracranial internal carotid artery calcifications were not independently related to the extent of white matter lesions or the presence of stroke. In a follow-up study of 72 patients, Taoka et al 13 did not find an association between the intracranial internal carotid artery calcifications score and the later occurrence of stroke. Therefore, they concluded that intracranial calcifications should not be considered as the cause of an ischemic event by being a source of embolism or thrombosis, but they should be considered as a marker of systemic atherosclerotic disease, which is closely related to stroke.…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, previous studies made use of a qualitative grading system. [8][9][10][11][12] Although Taoka et al 13 used commercially available software to assess the Agatston score of intracranial calcifications, they had to eliminate the contamination of bone attenuation on wide-windowed CT images. We developed custom-made software for quantification of intracranial calcifications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations